Who were the plunderers of Salmydessus? - Vasilev, Miroslav Ivanov, (Access archaeology., 2022)
A discussion of ten references (from different periods) concerning the piratical activities of the Thracians at Salmydessus in an attempt to identify who these Thracians were. It is a historical work, with a strong element of Quellenforschung, and provides a comprehensive examination of the literary and epigraphic evidence relevant to the topic.